Biofacies Analysis of the Upper Oligocene Deposits (Qom Formation) in Urumieh Dokhtar Zone, Iran - Moghadam, Iraj Maghfori (2019)
In order to determine the accurate paleoenvironmental conditions of Qom Formation, one stratigraphic section was studied in the Urumieh-Dokhtar Zone (West of Ashtian). 60 thin sections of the Qom Formation, 71 m thick, were prepared and the distribution of benthic foraminifera was analyzed. On the basis of the recognized foraminifera, the age of Qom Formation in the studied section is assigned to the Late Oligocene (Chattian). In this study, sex different biofacies and two lithofacies types have been recognized, that can be grouped into two depositional environments, back ramp (alluvium channel, lagoon and shoal) and the ramp (inner, middle and outer ramp). The alluvium channel is characterized by Gms (gravel with massive layering and abundant matrix). The shoal is represented by fine to medium sandstone: calcite cemented submature litharenite. The lagoon is dominated by the presence of bioclastic bryozoan corallinacea wackestone- packstone and bioclastic foraminifera corallinacean wackstone to packstone. The inner ramp is characterized by bioclastic benthic foraminifera (perforate and imperforate) wackestone-packstone and the middle ramp represented by bioclastic perforate foraminifera wackstone-packstone and bioclastic Operculina packstone. Outer ramp is characterized by bioclast benthic and planktonic foraminifera mudstone.